ETHNOBOTANICAL SURVEY OF MEDICINAL PLANTS USED IN THE TREATMENT OF MALARIA BY THE IDOMA SPEAKING PEOPLE OF OGBADIBO LOCAL GOVERNMENT AREA OF BENUE STATE, NIGERIA - Madara, A. A.; Abah, R. O.; Elkanah, O. S. (FUDMA JOURNAL OF SCIENCES, 2023)
Ethnobotanical survey of medicinal plants used by the Idoma speaking people of Ogbadigbo local government area of Benue State for treatment of malaria was carried out. The survey was aimed at identifying the plants used in the treatment of malaria among the Idoma people. Information was collected by interviewing indigenous Idoma herbal medicine practitioners, herb sellers, and farmers making use of interviews and structured questionnaire. A total of 37 plant species belonging to 22 families were recorded from the surveys that are being used in herbal antimalarial recipes. Fabaceae and Combretaceae were most represented with 4 species each (10.8%), followed by Rubiceae, Malvaceae, Euphobiciceae, Anarcardiaceaea, Moraceae, Meliceae, Annoniceae, Phyllanthaceae and Lamiaceae represented by 2 species each (5.4%) while the remaining 11 families had 1 species each (2.7%). Investigations included the plant parts used, methods of preparing the herbal antimalarial recipe and how they are administered. The results indicated that the parts of the plants used could be the leaves, stem bark, roots or whole plant. Water was the main medium of antimalarial recipe preparations, irrespective of the part, whole plant or combination of parts of plant used. Though, a large number of plants that are traditionally used for the treatment of malaria were identified, scientific validation of claims of antimalarial potency is required.